2016
DOI: 10.1089/jmf.2015.0098
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Applications ofMucuna pruriensPeptide Fractions Purified by High-Performance Liquid Chromatography as Angiotensin-Converting Enzyme Inhibitors, Antioxidants, Antithrombotic and Hypocholesterolemic Agents

Abstract: A Mucuna pruriens protein concentrate was hydrolyzed with a digestive (pepsin-pancreatin) enzymatic system. The soluble portion of the hydrolysate was fractionated by ultrafiltration and the ultrafiltered peptide fraction (PF) with lower molecular weight was purified by reversed-phase high-performance liquid chromatography. The PF obtained were evaluated by testing the biological activity in vitro. Fractions showed that the ability to inhibit the angiotensin-converting enzyme had IC50 values that ranged from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
2
8
0
Order By: Relevance
“…These results are similar to those of Gallegos et al ., who affirmed that antioxidant activity is higher in the lower size fractions, compared with the higher size, and is attributed to the presence of aromatic amino acids, as also indicated by Herrera‐Chalé et al . Likewise, the ultrafiltered fractions with the lowest protein content presented the highest antioxidant response and with statistically significant differences relative to the other compounds.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results are similar to those of Gallegos et al ., who affirmed that antioxidant activity is higher in the lower size fractions, compared with the higher size, and is attributed to the presence of aromatic amino acids, as also indicated by Herrera‐Chalé et al . Likewise, the ultrafiltered fractions with the lowest protein content presented the highest antioxidant response and with statistically significant differences relative to the other compounds.…”
Section: Resultssupporting
confidence: 92%
“…These results are similar to those of Gallegos et al, 31 who affirmed that antioxidant activity is higher in the lower size fractions, compared with the higher size, and is attributed to the presence of aromatic amino acids, as also indicated by Herrera-Chalé et al 32 Likewise, the ultrafiltered fractions with the lowest protein content presented the highest antioxidant response and with statistically significant differences relative to the other compounds. Herrera Chalé et al 8 evaluated the antioxidant activity of the protein derivatives from M. pruriens L. and found that F<1 kDa and F1-3 kDa had a higher activity (709 mmol L −1 mg −1 and 537 mmol L −1 mg −1 respectively) than the total hydrolysate and the larger fractions F5-10 kDa and F-10 kDa (102 mmol L −1 mg −1 , 222 mmol L −1 mg −1 , and 10.12 mmol L −1 mg −1 respectively).…”
Section: Protein Content and Dhsupporting
confidence: 90%
See 2 more Smart Citations
“…Of the wide range of legumes belonging to the family Febaceae, Mucuna pruriens , known as velvet bean, stands out for its high protein content (20%–35%) in its seeds (Brunner, Beaver, & Flores, ). Previous research studies done in protein hydrolysates and peptide fractions of M. pruriens showed effects on inhibition of angiotensin‐converting enzyme, hypotensive, and antioxidant activities (Herrera‐Chalé, Ruiz‐Ruiz, Betancur‐Ancona, & Segura‐Campos, ); moreover, small‐sized peptide fractions such as 3–5 and 1–3 kDa have shown anti‐inflammatory activity decreasing the production of proinflammatory cytokines such as TNF‐α and IL‐6 on peritoneal murine macrophages. These results suggest protein hydrolysates and peptide fractions as possible nutraceuticals or alternative treatment for chronic non‐communicable disease such as TD1 (Martínez‐Leo, Arana‐Argáez, Acevedo‐Fernández, Moo‐Puc, & Segura‐Campos, ).…”
Section: Introductionmentioning
confidence: 98%